Global Health Curricula in Ophthalmology Residency Programs in the United States - Ponsetto, Momoko K.; Siegel, Nicole H.; Desai, Manishi A.; LaMattina, Kara C. (Journal of Academic Ophthalmology, 2021)
Objective The aim of the study is to investigate the design, content, and administration of global health curricula within ophthalmology residency programs in the United States (U.S.) and share the curriculum utilized in the Department of Ophthalmology at Boston University School of Medicine (BUSM).Design A survey designed through the Association of University Professors in Ophthalmology platform was emailed to residency program directors at 106 accredited ophthalmology residency programs.Setting BUSM Department of Ophthalmology, Boston, MA. Tertiary clinical care.Participants Twenty-eight ophthalmology residency program directors responded, which represent 26% of the total number of residency programs in the United States. Twenty-seven programs fully completed the survey, and one program partially completed the survey.Results Of the respondents, three programs do not include global health curricula. The most common curricular elements included are: lectures (n = 15, 60%); wet laboratories (n = 10, 40%); and journal clubs (n = 9, 36%). In terms of annual frequency, global health activities occur: twice a year (n = 12, 46%); less than once a year (n = 10, 39%); or every few months (n = 4, 15%). Fewer than half of programs (n = 10, 42%) incorporate local outreach at least once a year into their program. Twelve programs (48%) do not incorporate ethics-related topics, while the 13 remaining programs (52%) incorporate them at least once annually. The most common curricular topic is surgical techniques, with manual small incision cataract surgery (MSICS) being the most frequently emphasized (n = 17, 68%).Conclusion A robust global health curricula combined with a hands-on international component can contribute to a well-rounded training experience. Many ophthalmology residency programs value the importance of incorporating global health into their residents' training. The most common elements of global health curricula in U.S. ophthalmology residency programs included are teaching of surgical techniques for resource-limited settings and international electives. Further investigation into the impact of different components of a global health curriculum on both resident experience and international partnerships is warranted.
Keywords: global health; international health; ophthalmology residency; outreach; ethics; curriculum; curricula